PERINEAL ECTOPIC TESTIS - A RARE ANOMALY WITH EMPTY SCROTUM - Safdar Hussain Awan (Army Medical College Rawalpindi, 2020)
Undescended testis is a very common presentation in male paediatric population but testis at ectopic sites is a very rare pathology. One of the ectopic sites is perineum and it accounts for only 1% of all cases of undescended testis. We report a case of an 11yr old boy who presented with an empty left hemiscrotum and detailed examination revealed a soft tissue mass on the corresponding side in the perineum. Surgical exploration was carried out during which it was revealed that mass was actually testis at ectopic site with adequate length of the spermatic cord. Testis was mobilized and fixed in the ipsilateral hemiscrotum.